2021
DOI: 10.1186/s12863-021-00996-x
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq analysis in giant pandas reveals the differential expression of multiple genes involved in cataract formation

Abstract: Background The giant panda (Ailuropoda melanoleuca) is an endangered mammalian species native to China. Fewer than 2500 giant pandas are known to exist, many of which are bred in captivity as a means to preserve and repopulate the species. Like other captive mammals, giant pandas acquire age-related cataracts, reducing their quality of life. Recent comparative genome-wide methylation analysis revealed 110 differentially methylated genes associated with cataract formation including six also asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The development of age-related cataracts is mainly promoted by environmental factors that cause oxidative damage to DNA and proteins 5 – 7 , 9 . This triggers changes in DNA methylation and gene expression, and in previous studies we and others have identified target genes involved in apoptosis, DNA repair and oxidative stress responses that may represent an attempt to counter or reverse the damage that occurs during cataract formation 17 , 18 , 24 – 26 .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The development of age-related cataracts is mainly promoted by environmental factors that cause oxidative damage to DNA and proteins 5 – 7 , 9 . This triggers changes in DNA methylation and gene expression, and in previous studies we and others have identified target genes involved in apoptosis, DNA repair and oxidative stress responses that may represent an attempt to counter or reverse the damage that occurs during cataract formation 17 , 18 , 24 – 26 .…”
Section: Discussionmentioning
confidence: 85%
“…Epigenetic modifications such as DNA methylation can directly affect transcription, and we have previously reported correlations between the methylated loci detected in panda cataracts and the modulation of gene expression in affected vs unaffected individuals 17 , 18 . However, the regulation of gene expression at the level of protein synthesis and turnover means that transcript and protein levels often do not correlate directly, and this is particularly relevant in the lens where the proteome is known to have a very slow turnover compared to non-lens tissues in the eye, suggesting that serum markers of cataract formation may not track closely with mRNA levels 27 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation